Perceived Discrimination and Life Satisfaction of Elderly Chinese People: The Chain Mediating Effects of National Identity and Sense of Community - Yao, Jin; Yang, Liping; Han, Xiaoxia; Li, Yiying (Frontiers in Psychology, 2018)
In China, aging is becoming an increasingly serious issue, and the Chinese are paying more attention to the life satisfaction of the elderly. Nevertheless, in their daily lives, the elderly in China often perceive discrimination, which may negatively influence their life satisfaction. To enable a better understanding of these relationships, we discuss the factors affecting the macro-system (national identity) and micro-system (sense of community) of the elderly. Three hundred and ninety-one old people (60–101 years old; 121 males, 270 females) from three communities in the Anhui and Shandong provinces of China were took part in our study, each completing adapted versions of a perceived discrimination measure, national identity questionnaire, sense of community questionnaire, and life satisfaction questionnaire. The results of structural equation modeling revealed that perceived discrimination negatively influenced life satisfaction through national identity and community. The total mediation effect was 32.17%. Perceived discrimination was found to negatively predict national identity, suggesting that perceived discrimination brings a negative influence to national identity within Chinese culture, which was at macro-system. The relationship between perceived discrimination and life satisfaction was partially mediated by the chain of national identity and sense of community. The relationship between perceived discrimination and life satisfaction, when mediated by national identity or sense of community, was not significant. This suggests that the rejection–identification model cannot be applied to the Chinese elderly. The limitations of our study and the implications of its results were be consider in discussion.